Systematic mediation and interaction analyses of kidney function genetic loci in a general population study - Dariush Ghasemi-Semeskandeh; David Emmert; Eva König; Luisa Foco; Martin Gögele; Mohamed S. Sarhan; Laura Barin; Ryosuke Fujii; Christian Fuchsberger; Dorien J. M. Peters; Peter P. Pramstaller; Cristian Pattaro (PLoS ONE, 2025)
Chronic kidney disease (CKD) is a complex disease affecting >10% of the global population, with large between- and within-continent variability reflecting major environmental determinants. To identify molecular targets for treatment and prevention, genome-wide association study meta-analyses (GWAMAs) of CKD-defining traits have identified hundreds of genetic loci in aggregated population samples. However, while GWAMAs estimate the average allelic effect across studies, single population studies may be relevant to unravel specific mechanisms. To assess whether a study sample from a specific population could extend existing knowledge on kidney function genetics, we selected 147 kidney function relevant loci identified by a large GWAMA, assessing their association with the glomerular filtration rate estimated from serum creatinine (eGFRcrea) in 10,146 participants to the Cooperative Health Research In South Tyrol (CHRIS) study, conducted in an Alpine region where thyroid dysfunction is common. We identified associations with single nucleotide polymorphisms (SNPs) at 11 loci, showing up-to-5.4 times larger effect sizes than in the corresponding GWAMA, not explainable by allele frequency differences. Systematic mediation analysis across 70 quantitative traits identified serum magnesium and the activated partial thromboplastin time as partial mediators of the eGFRcrea associations at SHROOM3 and SLC34A1 , respectively. Given that free triiodothyronine and thyroxine acted as effect modifiers across all loci, we conducted SNP-by-thyroid stimulating hormone (TSH) interaction analyses, identifying significant interactions at STC1 : SNPs had larger effects on eGFRcrea at higher TSH levels, possibly reflecting stanniocalcin-1 autocrine and paracrine role. Individual population studies can help characterize genetic associations. The interplay between phenotypes at SHROOM3 and SLC34A1 and the role of thyroid function as a genetic effect modifier warrant further investigations.